Law as General Rule or Law as Conglomeration of Legal Decision - Moh. Rif'an; Muhammad Akbar Nursasmita; Fazal Akmal Musyarri; Danang Wahyu Setyo Adi; Elsa Assari (CV Rewang Rencang, 2020)
In the world, there are two legal systems that are widely used by countries, namely Civil Law or Continental Europe and Common Law or Anglo Saxon. The two legal systems have their own characteristics that result in advantages and disadvantages. Simply put, civil law requires legal certainty with the use of laws and regulations as the main reference. While Common Law demands the newness of the law in accordance with the conditions of the community by relying on the consideration of the judge's decision to the previous ruling. This, of course, provokes philosophical opposition and forces the mind to choose which system is most ideal to use. In this paper, the author attempts to comprehensively analyze the dilemma between the two legal systems.